PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN BELANJA MODAL TERHADAP PENDAPATAN PER KAPITA KABUPATEN/KOTA PROVINSI SUMATERA SELATAN - Wigamas Rania Aliya; Henny Yulsiati; Yuli Antina Aryani (Institut Pendidikan Alfatah Mataram, 2024)
Abstract: The purpose of this study was to analyze the effect of Regional Original Income, General Allocation Funds and Capital Expenditures on Per Capita Income of Regency/City Governments in South Sumatra Province. The sample used is 17 regencies/cities in South Sumatra Province. Sampling was carried out using the saturated sampling or using all members of the population as samples. Data were collected by documentation method in the form of secondary data. The instrument used in this research is the Eviews 10. The results of the study show that Regional Original Income has no and no significant effect on Per Capita Income, General Allocation Funds have a negative and significant effect on Per Capita Income, and Capital Expenditures have a negative but not significant effect on Per Capita Income of Regency/City Governments in South Sumatra Province.